2019
DOI: 10.1016/j.cllc.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant EGFR Mutation and EML4-ALK Rearrangement in Lung Adenocarcinoma Is More Frequent in Multifocal Lesions

Abstract: We retrospectively investigated the intertumoral heterogeneity of pathologic and genetic characteristics of multifocal lung adenocarcinomas (LUAC) with epidermal growth factor receptor (EGFR)/anaplastic lymphoma kinase (ALK) co-alterations. The prevalence of EGFR/ALK co-alterations was higher in the multifocal LUAC than in the unifocal LUAC. To determine appropriate treatment strategies, extensive molecular profiling could give us more information to distinguish primary lesions from metastatic lesions. Backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…While there was no primary tumor imaging feature unique to METex14-mutated NSCLC in our cohort, there was an increased frequency of multifocality, with more than one in five patients having multifocal adenocarcinoma at the time of initial presentation ( Figure 2). This incidence was higher than the prevalence of ALK and concomitant ALK and EGFR alterations in multifocal lung adenocarcinomas [52]. It is possible that the multifocality reflects multiple synchronous adenocarcinomas with distinct splice site mutations, a finding which has been previously described in the literature for METex14-mutated primary lung adenocarcinomas [53].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…While there was no primary tumor imaging feature unique to METex14-mutated NSCLC in our cohort, there was an increased frequency of multifocality, with more than one in five patients having multifocal adenocarcinoma at the time of initial presentation ( Figure 2). This incidence was higher than the prevalence of ALK and concomitant ALK and EGFR alterations in multifocal lung adenocarcinomas [52]. It is possible that the multifocality reflects multiple synchronous adenocarcinomas with distinct splice site mutations, a finding which has been previously described in the literature for METex14-mutated primary lung adenocarcinomas [53].…”
Section: Discussionmentioning
confidence: 53%
“…Multifocal adenocarcinomas at presentation may help indicate the possibility of METex14-mutated NSCLC and lead to more rapid triaging for molecular screening. These synchronous lung adenocarcinomas are increasingly being recognized and can be a diagnostic and management challenge [52]. Detection of these potentially targetable mutations in multifocal NSCLC may prove to be beneficial when these malignancies progress and metastasize.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there were more lymph node metastasis in patients with multiple ALK gene fusion-positive lesions and more patients with N2 stage tumors. Furthermore, in our retrospective study, metastatic lesions in lymph node were driven by ALK rearrangement rather than EGFR mutation in four cases [6,8]. All these results suggested that ALK probably played a key role in tumor metastasis of multifocal Lung Adenocarcinoma Harboring EGFR/ALK co-alteration.…”
Section: Discussionmentioning
confidence: 57%
“…The prevalence and clinical relevance of EGFR/ALK co-alterations in multifocal adenocarcinomas required detailed investigation as well. Our previous study showed that concomitant EGFR mutation and ALKrearrangement in synchronous multifocal lung adenocarcinomas was more frequent [8]. Here, we reported a case of patient who diagnosed with multifocal lung adenocarcinomas exhibiting both EGFR mutation and EML4-ALK rearrangement, in order to give some helpful advices for the clinical practice.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, several studies have emerged which use different molecular biology techniques to analyze SMLC. These include comparative genomic hybridization (CGH), DNA microsatellite analysis, and next-generation sequencing (NGS) [12][13][14] . Generally, tumors with similar molecular characteristics are believed to be IM with a monoclonal origin.…”
Section: Discussionmentioning
confidence: 99%